Blessed are those that hunger and thirst for righteousness Sharpening the ethical dimension of prophetic preaching in a context of corruption - De Wet, Fritz; Kruger, Ferdinand (2013)
The prevalence of corruption has enormous negative consequences for the ideal of an orderly and peaceful society. Corruption does not only have a destructive impact on socio-economic life, but also on human relationships, value systems and vision for life. With this research the authors described the role of the ethical dimension of prophetic preaching in addressing the apparent lack of righteousness as it manifests in a context of corruption in the South African society. The problem field was explored with the focus on an apparent lack of vision and willingness to hunger and thirst for righteousness in the current manifestation of corruption in the South African society. Normative perspectives from Scripture (attempting to voice the impact of Jesus’ words in the Beatitudes, with the focus on Matthew 5-6) were discussed. It is reasoned that Jesus’ words pneumatologically proved to be essential in developing a sharpened and action-inducing vision of the righteousness of the kingdom of God breaking through in the praxis of a society struggling with the effects of corruption. The research culminated in the formulation of preliminary homiletic theory with a view to a vision for a kind of prophetic preaching that will be able to activate the consciousness of hungering and thirsting for the righteousness of God’s kingdom and lead the believer in a life culminating in blessed nourishment. The ethical dimension of prophetic preaching is anchored in the eschatological sphere, aimed at making the perceiver conscious of the distinct presence of the King, calling his people to a blessed presence in this world and empowering them with his promise of restoration of an abundant life for all.
Keywords: Corruption